Congenital Anomalies of Superior Vena Cava and their Implications in Central Venous Catheterization. Issue 4 (July 2015) - Rossi, Umberto G.; Rigamonti, Paolo; Torcia, Pierluca; Mauri, Giovanni; Brunini, Francesca; Rossi, Michele; Gallieni, Maurizio; Cariati, Maurizio
Congenital anomalies of superior vena cava (SVC) are generally discovered incidentally during central venous catheter (CVC) insertion, pacemaker electrode placement, and cardiopulmonary bypass surgery. Persistent left SVC (PLSVC) is a rare (0.3%) anomaly in healthy subjects, usually asymptomatic, but when present and undiagnosed, it may be associated with difficulties and complications of CVC placement. In individuals with congenital heart anomalies, its prevalence may be up to 10 times higher than in the general population. In this perspective, awareness of the importance of the incidental finding of PLSV during CVC placement is crucial. To improve knowledge of this rare but potentially dangerous condition, we describe the embryological origin of SVC, its normal anatomy, and possible congenital anomalies of the venous system and of the heart, including the presence of a right to left cardiac shunt. Diagnosis of PLSVC as well as the clinical complications and technical impact of SVC congenital anomalies for CVC placement are emphasized.